The British critic: Volume 8(1796) (Printed for F. and C. Rivington, 1796)
[Review of] Lyrical ballads, with a few other poems / [Francis Wrangham], vol. XIV, no. IV, Oct. 1799, pp. 364-369 -- [Review of] Wallenstein. A drama. In two parts. Translated from the German of Frederick Schiller, by S.T. Coleridge, vol. XVIII, no. V, Nov. 1801, pp. 542-545.